Design and Development of the RPG Game Novus: A Sole Remnant as a Stem Learning Media Focused on Basic Mathematics Using Godot Engine - Kevin Valeri; Gerry Firmansyah; Agung Mulyo Widodo; Habibullah Akbar (Eduvest - Journal of Universal Studies, 2026)
The integration of Science, Technology, Engineering, and Mathematics (STEM) education has become increasingly important in developing students’ critical thinking, problem-solving, and innovation skills. However, elementary school students often experience difficulties in mathematics learning due to conventional teaching methods, low engagement, and mathematics anxiety. This study aims to design and develop Novus: Sole Remnant, a narrative Role-Playing Game (RPG) built with the Godot Engine, as a STEM-oriented learning medium focused on basic mathematics for elementary school students. The research employed a hybrid methodology combining Research and Development (R&D) and Research through Design (RtD) approaches. Data were collected through observations, in-depth interviews, documentation, and qualitative evaluations involving elementary school teachers, students, and casual gamers using purposive sampling techniques. The findings indicate that the game successfully integrates mathematical concepts into gameplay through diegetic learning, allowing students to engage with arithmetic and number pattern challenges naturally within the narrative context. The implementation of visual scaffolding features effectively supported independent learning and enhanced conceptual understanding, while the checkpoint and respawn mechanisms reduced mathematics anxiety and encouraged a growth mindset. Teachers also confirmed the game’s alignment with the Independent Curriculum and its potential as an alternative homework medium. In conclusion, Novus: Sole Remnant demonstrates strong potential as an engaging, pedagogically effective, and technologically feasible digital learning tool for improving elementary mathematics learning and supporting STEM education.